The Role of Immigration: Race/Ethnicity and San Diego Homicides Since 1970 - Martinez, Ramiro (Journal of quantitative criminology, 2016)
Objectives The temporal variation in homicide is examined by studying trends in race/ethnic specific killings (e.g. Blacks, Latinos and Whites). Two substantively important issues are also addressed—a closer examination of the role community heterogeneity plays in homicide levels and the treatment of immigration as an endogenous social process. Methods Data are reported homicides in the city of San Diego, California over the period 1960–2010. The address of each killing is geocoded into 341 census tracts. Results We find that neighborhoods experiencing increases in the foreign-born population tend to be less violent. White and Latino homicide victimization was reduced significantly as a product of increases in the neighborhood concentration of foreign-born individuals. Supplementary analyses did not find empirical evidence that the influx of foreign-born individuals could (or should) be considered a disruptive social process. Over the past five decennial census periods, the exponential increase in immigration in this border city is not associated with an increase in homicide victimization. Conclusions When examined through a wider temporal lens than is typically employed, and accounting for the endogeneity of immigrant residential settlement, we find no support for the claims that immigration is a crime generating social process.